2021
DOI: 10.3151/jact.19.433
|View full text |Cite
|
Sign up to set email alerts
|

Calcite Precipitation at Cement–Bentonite Interface. Part 1: Effect of Carbonate Admixture in Bentonite

Abstract: Calcium leaching from cementitious materials into bentonite is a key process for the long-term alteration of cement-clay interfaces of engineered barrier systems. Strong chemical gradients between cement and clay drive the precipitation of minerals such as calcium silicate hydrate (C-S-H) and calcite. To analyze the mineralogical and porosity evolution at the cement-clay interface, composite specimens consisting of cement paste and bentonite mixed with various amounts of sodium carbonate were subjected to imme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 74 publications
(82 reference statements)
1
1
1
Order By: Relevance
“…This indicates that 14 Å tobermorite can potentially form during the alteration of bentonite close to cementitious materials with Stage I and II alkaline leachates (Table 5). Contrary to this, the formation of 14 Å tobermorite has not been reported in previous laboratory and in situ experiments showing alkaline alteration of bentonite or clay, but rather the formation of C-S-H, C-A-S-H, 11 Å tobermorite, or Al-tobermorite (Fernández et al, 2016;Lalan et al, 2016;Fernández et al, 2017;Lerouge et al, 2017;Nakarai et al, 2021;Ramírez et al, 2005;Sánchez et al, 2006;Yokoyama et al, 2011;Techer et al, 2012). The tendency for C-S-H to form at low temperatures was recognized from these experiments, which lasted up to 15 y (Appendix A in the Supplementary material).…”
Section: Calcium Silicatescontrasting
confidence: 81%
“…This indicates that 14 Å tobermorite can potentially form during the alteration of bentonite close to cementitious materials with Stage I and II alkaline leachates (Table 5). Contrary to this, the formation of 14 Å tobermorite has not been reported in previous laboratory and in situ experiments showing alkaline alteration of bentonite or clay, but rather the formation of C-S-H, C-A-S-H, 11 Å tobermorite, or Al-tobermorite (Fernández et al, 2016;Lalan et al, 2016;Fernández et al, 2017;Lerouge et al, 2017;Nakarai et al, 2021;Ramírez et al, 2005;Sánchez et al, 2006;Yokoyama et al, 2011;Techer et al, 2012). The tendency for C-S-H to form at low temperatures was recognized from these experiments, which lasted up to 15 y (Appendix A in the Supplementary material).…”
Section: Calcium Silicatescontrasting
confidence: 81%
“…As per Figure 4, it can be observed that the reaction temperature for several modified GCC falls within the range of 200 °C-300 °C, as Frontiers in Materials frontiersin.org reported in studies by Yuan et al (2019) and Nakarai et al (2021). Upon comparing the curve of unmodified GCC with the curves of modified GCC, it is evident that unmodified GCC shows minimal mass loss and remains relatively stable as the temperature increases in the temperature range of 200 °C-600 °C, while modified GCC exhibits varying degrees of mass loss with the increase of temperature, and the extent of mass loss roughly corresponds to the amount of modifying agent added.…”
Section: Modification Mechanism Analysissupporting
confidence: 72%
“…The addition of carbonates to clay-like LWAs increased the content of calcium ions, and the strong chemical gradient between cement and clay promoted the formation of C-S-H gels and other white precipitation products [ 29 , 60 ]. In this way, self-healing is initiated.…”
Section: Components and Mechanisms Of Lightweight Aggregate Self-heal...mentioning
confidence: 99%